NONVERBAL CODES IN ENGLISH CLASSROOM INTERACTION: ETHNOGRAPHIC STUDY AT STATE ISLAMIC COLLEGE (STAIN) PAREPARE - Amzah Selle (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
The use of nonverbal codes in communication in classroom causes the effectiveness of teaching and learning interaction in classroom, especially in English classroom interaction in STAIN Parepare. This research can give description and information to improve teachers’ behaviors’ in teaching and learning interaction in classroom. It also can be a part of culture in teaching and learning environment in campus. This research is conducted in English education study program. The design of the research is ethnography study. The research takes two English teachers as data resources. It used observation in collecting data. In analyzing data, the researchers used Constant Comparative Methods. The research findings show the teachers nonverbal codes in English classroom interaction include: (1) gesture such as gesture while talking to the classroom moves around the classroom while teaching, and has a relaxed body position while talking to the class.; (2) eye movement such as looks at the class while talking; and (3) smiles at the class while talking.